Penegakan Hukum Tindak Pidana Korupsi yang Berbarengan dengan Tindak Pidana Pencucian Uang (Concurrcus Realis) - Suhardi, Suhardi; Sudjiarto, Tatok; Hutahaean, Armunanto (Syntax Literate, 2023)
The purpose of this research is to contribute ideas and enrich the concepts and understanding of legal theories regarding Corruption Crimes committed by state officials, especially regarding law enforcement based on Law no. 20 of 2001 in conjunction with Law no. 31 of 1999 concerning the Eradication of Corruption Crimes. For the development of science, to provide an overview and input regarding investigations into criminal acts of corruption by the police. This research uses normative juridical research which only uses secondary data as data sourced from primary legal materials and secondary legal materials. The role of the suspect Ervan Fajar Mandala as properly regulated in the Supreme Court decision Number: 1621 K/Pidsus/2013. Because the unlawful act has been proven to fulfill the elements as stipulated in Article 2 paragraph (1) and or Article 3 of Law No. 31 of 1999 concerning the Eradication of Corruption in conjunction with Law no. 20 of 2001 concerning changes to Law no. 31 of 1999 concerning the Eradication of Corruption Crimes and/or Article 3 of RI Law No.15 of 2002 concerning Money Laundering Crimes as amended by RI Law No. legally and convincingly committed the crime of corruption together with the crime of money laundering.